الطعن بطريق إعادة المحاكمة في أحكام القضاء الإداري الفلسطيني دراسة تحليلية مقارنة - بعلوشة, شريف (جامعة الوادي University of Eloued, 2019)
ملخص البحث أخذ المشرع الفلسطيني بمبدأ التقاضي على درجتين أمام القضاء النظامي، وأجاز الطعن في الأحكام الصادرة في المنازعات المدنية والجزائية سواء بطرق الطعن العادية أو غير العادية، إلا أنه لم يأخذ بهذا المبدأ أمام القضاء الإداري، ولم ينص في الأصول المطبقة أمام محكمة العدل العليا على أي طريق من طرق الطعن في الأحكام الإدارية، ولم يحلْ لأي قانون آخر، وبالتالي لم يأخذ المشرع بمبدأ التقاضي على درجتين في الدعاوى الإدارية، الأمر يُثير التساؤل عن مدى جواز الطعن بطريق إعادة المحاكمة في أحكام محكمة العدل العليا الفلسطينية في حال توافرت إحدى حالات أو أسباب إعادة المحاكمة التي نص عليها قانون أصول المحاكمات المدنية والتجارية، أو قانون الإجراءات الجزائية الفلسطيني، لذا تناولنا الأحكام الموضوعية والإجرائية لإعادة المحاكمة بالدراسة والتحليل، وخلصنا إلى أنه يجوز الطعن بطريق التماس إعادة المحاكمة في أحكام محكمة العدل العليا الفلسطينية وذلك أعلاءً لمبدأ المشروعية، وتحقيقاً للعدالة، ويجب على القضاء الإداري الفلسطيني إعمال صلاحياته في ابتداع القواعد والنظريات القانونية المتعلقة في السماح بالطعن بطريق إعادة المحاكمة إذا ما توافرت أي من حالاته، خاصة وأن هذا الطريق لا يتعارض وطبيعة الدعاوى الإدارية، وندعو المشرع الفلسطيني إلى ضرورة تنظيم القضاء الإداري وإجراءات التقاضي أمام المحاكم الإدارية الفلسطينية وجواز الطعن في أحكام القضاء الإداري بطرق العادية وغير العادية. Abstract The Palestinian legislator adopted the principle of two-tier litigation in front of the regular judiciary, and allowed the appeal of judgments that issued in civil and criminal disputes, either in ordinary or extraordinary methods of appeals, but it didn’t apply this principle in front of the administrative courts, and it wasn’t mentioned in the applied assets to the High Court of Justice on any way to appeal the administrative provisions, and it hasn’t been superseded by any other law, Thus, the legislator did not take the principle of two degree litigation in administrative proceedings, this raises the question of the extent of the possibility of appeal in the judgments in the retrial of the decisions of the Palestinian High Court of Justice in case of one of the cases or reasons of retrial which provided by civil and commercial law or the Palestinian Code of Criminal Procedures . So we addressed the substantive and procedural provisions for the retrial by studying and analyzing and concluded that a request for retrial can be appealed against the judgments of the Palestinian High Court of Justice in accordance with the principle of legality and for the sake of justice, The Palestinian administrative judiciary must fulfill its powers to create legal rules and theories concerning allowing retrial appeals if any of its cases is available. Especially this route does not conflict with the nature of administrative claims; we call on the Palestinian legislator to regulate the administrative judiciary, the procedures of litigation in front of the Palestinian administrative courts and the possibility of challenging the judgments of the administrative judiciary in ordinary and extraordinary ways.
Keywords: إعادة المحاكمة، إعادة النظر، القضاء الإداري، العدل العليا، الأحكام القضائية; retrial, reconsidering, administrative judiciary, higher justice, judicial decisions